2009
DOI: 10.1093/jjco/hyp008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center Phase II Trial of Weekly Paclitaxel Plus Cisplatin Combination Chemotherapy in Patients with Advanced Gastric and Gastro-esophageal Cancer

Abstract: Combination of weekly paclitaxel plus cisplatin is an active regimen with excellent tolerability as a first-line treatment of advanced gastric and gastro-esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Results showed that paclitaxel and its combination with paclitaxel delivered 23, 33, and 43% of response rate and 43, 23, and 40 months of 1-year survival with treatment of paclitaxel [50], paclitaxel plus carboplatin [48], and paclitaxel plus cisplatin [49], respectively. Polymeric paclitaxel micelles Genexol-PM [51] and NK105 [52] were also evaluated for efficacy and safety as Phase II trials. Results of the trials are shown in Table 13.…”
Section: Clinical Outcomes Of Polymer-paclitaxel Therapymentioning
confidence: 99%
“…Results showed that paclitaxel and its combination with paclitaxel delivered 23, 33, and 43% of response rate and 43, 23, and 40 months of 1-year survival with treatment of paclitaxel [50], paclitaxel plus carboplatin [48], and paclitaxel plus cisplatin [49], respectively. Polymeric paclitaxel micelles Genexol-PM [51] and NK105 [52] were also evaluated for efficacy and safety as Phase II trials. Results of the trials are shown in Table 13.…”
Section: Clinical Outcomes Of Polymer-paclitaxel Therapymentioning
confidence: 99%
“… 21 Moreover, a Phase II study has shown that weekly PTX plus DDP is an active regimen with excellent tolerability for advanced gastric and gastroesophageal cancer. 22 …”
Section: Introductionmentioning
confidence: 99%
“…With the increasing acceptance of Siewert's definition of AEG, more and more researchers have studied this clinicopathological entity 6 . However, most of the studies focused on histopathologic characteristics of AEG, surgical methods and outcomes of treatment [7][8][9][10][11] . To the best of our knowledge, there has been little investigation into the changes over time of the three subtypes of AEG.…”
Section: Introductionmentioning
confidence: 99%